THE USAGE OF ELECTRONEUROMYOGRAPHY FOR OPTIMIZATION DIAGNOSTIC APPROACHES TO PARKINSON’S DISEASE - Shkodina, A.D.; Tarianyk, K.A. (World of Medicine and Biology, 2022)
Motor and sensory symptoms in patients with Parkinson’s disease are usually measured by clinical scales with subjective assessments. That is why the development of new techniques and improvement of objective methodology is necessary for clinical practice. We conducted an analytical cross-sectional study based on the Parkinson's disease and other neurodegenerative diseases centre based on Poltava State Medical University in the period 2020–2021. We performed a factor analysis of features of electroneuromyography. We determined indicators and their relationships that characterize the tremor and the severity of the cubital syndrome on the dominant side, as well as the severity of the carpal syndrome on the non-dominant side in patients with Parkinson`s disease. Thus, the usage of factor loads determined by the results of our study allows optimizing the diagnostic approach to peripheral lesions in Parkinson`s disease by calculating the severity of tremor and tunnel neuropathies in these patients.
Keywords: Parkinson’s disease; tremor; carpal tunnel syndrome; cubital tunnel syndrome; electromyography; factor analysis